Training plus intensive consultation improves uptake and outcome expectations of prolonged exposure therapy among practitioners treating emergency service personnel with post-traumatic stress disorder. (June 2020) - Wade, Darryl; Terhaag, Sonia; Putica, Andrea; Metcalf, Olivia
Objective: Prolonged exposure (PE) therapy is an evidence-based psychological treatment of post-traumatic stress disorder (PTSD), yet uptake amongst practitioners is less than desirable. The aim of this study was to evaluate the efficacy of a PE training workshop plus intensive consultation programme to improve practitioners' self-efficacy and outcome expectations as well as uptake of PE for emergency service patients with PTSD. Method: Forty-five psychologists attended a PE training workshop in Sydney. Participants completed questionnaires at pre- and post-workshop and six-month follow-up. Results: The findings suggest that participation in the programme was associated with improvements in practitioners' beliefs in their ability to deliver PE to patients, an increase in their use of a range of PE components and an increase in their use of in vivo exposure with a greater proportion of patients. Conclusion: Effective training approaches for evidence-based treatments of PTSD should incorporate intensive consultation following training. Future studies should consider additional strategies to encourage practitioners to deliver PE to more patients with PTSD.